OPEN RADICAL RETROPUBIC PROSTATECTOMY - M. B. Chibichyan (Вестник урологии, 2018)
All aspects of radical major surgery for prostate cancer, performed by the retropubic way, are covered extensively in the lecture. It is shown for the practicing surgeon, complications of operations and ways of dealing with them. The current functional and cancer results of the operative intervention are described. There is no doubt that the present book will be very useful for urologists and oncologists by improving their skills in performing this type of radical prostatectomy.